POSSIBILITIES OF MARINE FISH CULTURE IN THE SALT-PAN AREAS AT TUTICORIN - Nair, R V; Bensam, P; Marichamy, R (Indian Journal of Fisheries, 2011)
The paper gives an account of the environmental conditions and the aquaticbiota in the salt-pan areas at Veppalodai, north of Tuticorin. Cultivable fishessuch as Chanos chanos, Mugil cephalus, the crab, Scylla serrata and the prawn,Penaeus indicus have been observed to thrive well. A seasonal fishery for C.chanos with an average annual yield of 4,000 kg is existing at present under conditions,when no controls are exercised for the normal growth and survival of thenaturally recruited stock which is open to the attack of predatory birds, crabs andsnakes. It is felt that the possibilities of culturing such species as C. chanos aregood under controlled conditions and safety from predators